HUBUNGAN PELAKSANAAN TOILET TRAINING YANG DILAKUKAN ORANG TUA TERHADAP KEJADIAN ENURESIS DIURNAL PADA ANAK - Norma Yuliana Saragih; Safri Safri; Sri Wahyuni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2020)
Enuresis is a term used for children who habitually wet their bed or urinateaccidentally or uncontrollably. One effort to overcome this problem is toilet training. Toilet training is an attempt to train children to be able to control and perform bowel movements and urination. The purpose of this study was to determine the correlation between the implementation of toilet training conducted by parents to the incidence of diurnal enuresis in children. This study uses an observational analytic research design and cross sectional approach. This research was conducted to children aged 6 to 7 years in Labuh Baru Barat Village, Pekanbaru, to 95 samples taken using non-probability sampling techniques, namely the purposive sampling method. The measuring instrument used was a questionnaire. The analysis used was univariate analysis and bivariate analysis with Chi square test. The results showed that the implementation of toilet training in the good category was 46 people (48.4%) and those who experienced enuresis were 8 people (8.4%). This shows that there is a significant correlation between the implementation of toilet training conducted by parents to the incidence of diurnal enuresis in children in Kelurahan Labuh Baru Barat with p value = 0.013 < α = 0.10. This research is expected to be a consideration for children, parents, and supporting references for future researchers. Keywords: children, diurnal enuresis, toilet trainingEnuresis is a term used for children who habitually wet their bed or urinateaccidentally or uncontrollably. One effort to overcome this problem is toilet training. Toilet training is an attempt to train children to be able to control and perform bowel movements and urination. The purpose of this study was to determine the correlation between the implementation of toilet training conducted by parents to the incidence of diurnal enuresis in children. This study uses an observational analytic research design and cross sectional approach. This research was conducted to children aged 6 to 7 years in Labuh Baru Barat Village, Pekanbaru, to 95 samples taken using non-probability sampling techniques, namely the purposive sampling method. The measuring instrument used was a questionnaire. The analysis used was univariate analysis and bivariate analysis with Chi square test. The results showed that the implementation of toilet training in the good category was 46 people (48.4%) and those who experienced enuresis were 8 people (8.4%). This shows that there is a significant correlation between the implementation of toilet training conducted by parents to the incidence of diurnal enuresis in children in Kelurahan Labuh Baru Barat with p value = 0.013 < α = 0.10. This research is expected to be a consideration for children, parents, and supporting references for future researchers. Keywords: children, diurnal enuresis, toilet training